Morphometry of Isan-Thai Clavicles as a Guide for Sex Determination - Kaewma,Ailadda (Sociedad Chilena de Anatomía, 2017)
The dried clavicles have been well documented to determine individual sex and age in many races. Such morphometric investigations in Isan (Northeastern) Thais have never been reported. Therefore, this study aimed to estimate the sex from dried clavicles of Isan-Thais using morphometric analysis. The identified 454 dried clavicles (254 males and 200 females), averaged age (60.69±14.36 years) were measured and analyzed for identification point (IP) and the demarking point (DP) values. The results showed that the identified-bone percentages by IP of the maximum clavicular lengths in males and females were 90.55 % (>139.9 mm) and 89 % (<140.6 mm). In addition, such percentages of the mid shaft circumference measured in male clavicles was 83.46 % (>37.7 mm) and in females was 75 % (<37.0 mm). However, percentages of the DP in all parameters were less than 50%. The highest DP values of maximum length of male clavicles was 43.31% (>152.5). In conclusion, the maximum length and mid shaft circumference investigated from this study can be used as basic data of Isan Thais for applying as a guide in forensic sciences for sex determination from dried clavicle remains.